2019
DOI: 10.1177/0361198118822820
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Movement Decision Model for Powered Two-Wheelers in Taiwan

Abstract: The maneuvering of powered two-wheelers (PTWs) is non-lane-based, and the interactions between PTWs and other vehicles in mixed traffic are complex. The behavior of PTWs, particularly in developing countries, is not the same as that of passenger cars, which has been studied for several decades. This study contributes to the existing literature on PTWs in several ways. A real-world microscopic vehicle trajectory database has been digitalized from a video clip for a four-lane urban arterial in Taipei (Taiwan). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Compared to a car driver, whose movement is relatively more constrained within a traffic lane, a motorcyclist occupies less road space, can ride with another peer motorcyclist within the same traffic lane, and can also perform lateral movement more easily and even undertake weaving maneuvers. This finding is along the same lines as those in the current literature on mixed traffic composed of motorcycles and automobiles ( 33 , 45 , 50 ).…”
Section: Aggressiveness Presented By Microscopic Kinematic Characteri...supporting
confidence: 89%
See 1 more Smart Citation
“…Compared to a car driver, whose movement is relatively more constrained within a traffic lane, a motorcyclist occupies less road space, can ride with another peer motorcyclist within the same traffic lane, and can also perform lateral movement more easily and even undertake weaving maneuvers. This finding is along the same lines as those in the current literature on mixed traffic composed of motorcycles and automobiles ( 33 , 45 , 50 ).…”
Section: Aggressiveness Presented By Microscopic Kinematic Characteri...supporting
confidence: 89%
“…Following Lee et al (44), we defined a weaving maneuver in this study as when a vehicle k, which is at the side (either left-hand or righthand side) of another vehicle v at time = T, was behind the vehicle v at any time points in the past 5 s (Figure 2a). In this definition, the behindness is strictly defined by whether the central front end of vehicle k was located between the virtual range formed by the lines extended from the rear right end and rear left end of the leading vehicle v. It should be noted that we assumed a buffer distance of 0.5 m to enlarge the virtual range because motorcycles do not strictly follow traditional lane discipline and can travel alongside or weave by another vehicle in the same lane (45). To operationalize this analysis on the weaving maneuver, we derived weaving maneuver frequencies (i.e., how many weaving maneuvers were performed) and employed the chi-square test to compare weaving maneuver frequencies by driver group (i.e., ODFD versus non-ODFD motorcyclists) and by time (i.e., non-meal-peak hours and meal-peak hours).…”
Section: Analysis Of Microscopic Kinematic Characteristicsmentioning
confidence: 99%
“…In addition to the aforementioned review of instrumented vehicle studies on driving behavior, several studies have collected the riding behavior of motorcycle riders using video cameras installed on road infrastructures and buildings, including maneuvering behavior along mixed traffic urban arterials [25][26][27][28]. However, only one study has been conducted on maneuvering behavior in queues at signalized urban intersections [5].…”
Section: Instrumented Vehicle Studies On Drivingmentioning
confidence: 99%
“…A lane selection model was developed in the form of a multinomial logit model, which could predict correctly about 78% of the maneuvers. Other similar studies (12)(13)(14)(15) have also shown promising results, however, these studies have just focused on the lateral behavior of the MTWs, and paid little to no attention to modeling the longitudinal behavior which eventually strongly affects the filtering prediction by MTWs. There has been some research focusing on ''overtaking'' behavior of MTWs, which specifically includes ''on-the-fly'' maneuvers and ''oblique'' (or multi-stage) maneuvers (7,(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%